(untitled) (Research, Society and Development, 2026)
Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most prevalent hereditary enzymopathy worldwide and represents a significant clinical challenge, particularly within pediatric practice. Although widely discussed in hematology, the condition remains underrecognized in routine pediatric care, leading to diagnostic gaps, inappropriate prescriptions, and an increased risk of hemolysis triggered by oxidative agents. This study conducted a narrative literature review aimed at identifying, classifying, and analyzing medications, vitamins, food dyes, and everyday substances capable of triggering hemolysis in pediatric individuals with G6PD deficiency.deficiency. Findings reveal substantial gaps in medical training, inconsistencies among scientific databases, and a lack of standardized safety recommendations, all of which hinder appropriate clinical decision-making. The review proposes an updated classification organized in frameworks (contraindicated, controversial/cautionary, and generally safe substances).